2017
DOI: 10.3390/ijerph14060574
|View full text |Cite
|
Sign up to set email alerts
|

A Three-Year Follow-Up Study of Antibiotic and Metal Residues, Antibiotic Resistance and Resistance Genes, Focusing on Kshipra—A River Associated with Holy Religious Mass-Bathing in India: Protocol Paper

Abstract: Background: Antibiotic resistance (ABR) is one of the major health emergencies for global society. Little is known about the ABR of environmental bacteria and therefore it is important to understand ABR reservoirs in the environment and their potential impact on health. Method/Design: Quantitative and qualitative data will be collected during a 3-year follow-up study of a river associated with religious mass-bathing in Central India. Surface-water and sediment samples will be collected from seven locations at … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2
1

Relationship

3
4

Authors

Journals

citations
Cited by 19 publications
(21 citation statements)
references
References 55 publications
(67 reference statements)
0
21
0
Order By: Relevance
“…Furthermore, study from Diwan et al reported the presence of ARG types (beta-lactams, quinolone etc.) from seven regular and three mass-bathing sampling points from the river Kshipra, Ujjain, India [91]. These findings from different studies irrespective of distinct source rivers represent commonality and reported to have the presence of mainly beta-lactam and tetracycline resistance genes.…”
Section: Discussionmentioning
confidence: 98%
“…Furthermore, study from Diwan et al reported the presence of ARG types (beta-lactams, quinolone etc.) from seven regular and three mass-bathing sampling points from the river Kshipra, Ujjain, India [91]. These findings from different studies irrespective of distinct source rivers represent commonality and reported to have the presence of mainly beta-lactam and tetracycline resistance genes.…”
Section: Discussionmentioning
confidence: 98%
“…The present study is a part of an ongoing project, which has been described in detail previously [15]. In brief, the study samples were collected from River Kshipra, in its 93 km flow through Ujjain district, before, during and after mass-bathing events.…”
Section: Study Setting and Sample Collectionmentioning
confidence: 99%
“…The pre-bathing samples were collected one day prior of the bathing event, post-bathing samples were collected 6-7 hours after bathing event while during-bathing samples were collected at the peak hours of the bathing event, generally between 9 to 11AM. Each time, riverwater and -sediment were collected in sterile screw-capped bottles and conical falcon tube respectively as described in detail [15]. Approximately 2Kg of sediment and 3.5L river-water were collected for analysis of water quality parameters, colony counts and antibacterial susceptibility as described elsewhere [15].…”
Section: Study Setting and Sample Collectionmentioning
confidence: 99%
See 2 more Smart Citations